Behavior of the Amazonian damselfly Chalcopteryx scintillans McLachlan (Zygoptera: Polythoridae) and comments on its morphological distinction from C. rutilans (Rambur) - Guillermo-Ferreira, Rhainer [UNESP]; Neiss, Ulisses Gaspar; Hamada, Neusa; Bispo, Pitágoras da Conceição [UNESP] (Taylor & Francis Ltd, 2014)
Polythorid damselflies are Neotropical stream dwellers, whose behavior has rarely been recorded. Here we describe the territorial and courtship behavior of Chalcopteryx scintillans McLachlan, an Amazonian damselfly with shiny copper-colored hind wings. Territorial behavior consists of aerial contests, when males engage in threat displays and mutual pursuits in ascending and rocking flights. During courtship, males hold their coppery hind wings still while hovering with their forewings, showing the hind wings to females, which hover in front of the male in response. After copulation, the male exhibits the courtship flight again by hovering over the oviposition resource (i.e. fallen tree trunk) on the stream. The females oviposit on the trunk while the males guard them by perching near and hovering around them constantly. We also present behavioral notes on reproductive and oviposition behavior, and comments on the differentiation between C. scintillans and C. rutilans (Rambur).
Keywords: Odonata; territoriality; dragonfly; reproduction; animal behavior; aquatic insect